Helheim Glacier diurnal velocity fluctuations driven by surface melt forcing. Issue 267 (6th February 2022) - Stevens, Laura A.; Nettles, Meredith; Davis, James L.; Creyts, Timothy T.; Kingslake, Jonathan; Ahlstrøm, Andreas P.; Larsen, Tine B.
Abstract: The influence of surface melt on the flow of Greenland's largest outlet glaciers remains poorly known and in situ observations are few. We use field observations to link surface meltwater forcing to glacier-wide diurnal velocity variations on East Greenland's Helheim Glacier over two summer melt seasons. We observe diurnal variations in glacier speed that peak ~6.5 h after daily maximum insolation and extend from the terminus region to the equilibrium line. Both the amplitude of the diurnal speed variation and its sensitivity to daily melt are largest at the glacier terminus and decrease up-glacier, suggesting that the magnitude of the response is controlled not only by melt input volume and temporal variability, but also by background effective pressure, which approaches zero at the terminus. Our results provide evidence that basal lubrication by meltwater drives diurnal velocity variations at Greenland's marine-terminating glaciers in a similar manner to alpine glaciers and Greenland's land-terminating outlet glaciers.